Pengaruh Profitabilitas, Leverage, dan Likuiditas terhadap Nilai Perusahaan dengan Struktur Modal sebagai Variabel Intervening pada Perusahaan Manufaktur yang terdaftar di BEI - Shoffia Anis Shantika; Imron Rosyadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The main goal of the company is to maximize the value of the company. Increasing the value of the company can also increase investment opportunities by investors, so the company can get a source of funds. This study aims to see and examine the effect of profitability, leverage, and liquidity on firm value with capital structure as an intervening variable. The research method used in this research is quantitative research method. The results of this study are (1) Profitability has a positive and significant effect on firm value. (2) Leverage and Liquidity have no significant effect on firm value. (3) Profitability and Leverage on firm value through capital structure have no significant effect. (4) Liquidity on firm value through capital structure has a significant influence.